Breaking the Monotony of Everyday Life in Early Modern Málaga - Reder Gadow, Marion (Cuadernos de Historia Moderna, 2015)
An extraordinary event alters the daily occupation of a city as that of Malaga. The witnesses of a passional crime report meticulously the incidents of the same one. Confirming the different testimonies there are traced the mobiles, the subjects and the circumstances that intervene directly or indirectly in this event, highlighting other collateral aspects as the collective mentality of the persons from Malaga before the death. The feminine look uses as conductive thread to compile information about a criminal act that has not come out in the annals of the city.